USING FORWARD CHAINING METHODS TO DIAGNOSE CHOLESTEROL DISEASE USING THE WEB - Venny Octavia; Jhonson Efendi Hutagalung jhonson; Cecep Maulana Cecep (Jurnal Teknik Informatika (Jutif), 2022)
Cholesterol disease can attack humans, both young and adult, in this case it is necessary to do a quick diagnosis to provide basic knowledge about cholesterol disease to sufferers. Advances in expert systems can overcome this problem, namely by designing a web-based computer system that is integrated with databases and programming languages ​​such as PHP-MySQL so that it can help cholesterol patients to diagnose the disease. The expert system application in its decision making uses a forward chaining inference engine where the goal driven data will start a search on the initial node to the goal node until it gets results. The results of the implementation of the system, namely the system provides questions in the form of symptoms that must be answered by the patient based on the symptoms experienced by the patient and the results of the process the system will provide information on what type of cholesterol disease he is experiencing in order to get a solution with treatment and handling. System that works with a knowledge base search that is able to provide decisions by utilizing an expert knowledge base.